Efektivitas Penerapan Software Accounting (Accurate) dalam Pengelolaan Laporan keuangan pada PT. XYZ (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the effectiveness of implementing Accurate accounting software in financial report management at PT. XYZ). Accurate is utilized to enhance operational efficiency, recording accuracy, and real-time financial reporting. The findings reveal that the use of Accurate reduces recording errors and accelerates the financial reporting process. Integration features across modules such as purchasing, sales, and inventory improve interdepartmental data consistency. Additionally, Accurate helps the company comply with Indonesian Financial Accounting Standards (PSAK) and tax regulations through automated reporting. Key success factors include adequate employee training and feature customization tailored to the needs of manufacturing companies. This study concludes that technology-based accounting software not only improves financial data accuracy but also supports better strategic decision-making for management.